“Entrenchment” processes: an ethnographic analysis of the dynamics and consolidation of the homeless - Bachiller, Santiago (Cuadernos de Trabajo Social, 2014)
Resulting from ethnographic field work with homeless people, the main goal of this article is to analyze the «entrenchment » processes that imply the consolidation of homelessness. Most homeless people would declare the streets are not their home. But, in order to survive and make things easier for them, daily they feel forced to appropriate particular public spaces. Such practices and discourses of appropriation usually represent the effort to make these public spaces to look like a home. These efforts are in vain and they show how, as the years pass, the limit that separates the street from home starts to fade out. These «entrenchment» processes are related to long term homelessness and the way in which it alters the subject’s perception and minimizes the chances of escaping from it.
Keywords: homeless; home; street; entrenchment process.